กรอบแนวคิดการพัฒนาการบริหารหลักสูตรส่งเสริมและพัฒนาศักยภาพนักเรียน ที่มีความสามารถพิเศษด้านดนตรี ของโรงเรียนวัดสุทธิวราราม - รังสิพุฒิกุล, สุนิสา; ชูประวัติ, เพ็ญวรา (An Online Journal of Education, 2018)
This research is a document research. The purpose is to review literature in conjunction with informal interviews. To lead the presentation of the conceptual framework for the development of curriculum development, promotion and development of talented students in music. (Arts-Music Study Plan) of Wat Sutthiwararam School (Grade 10 - 12). The research contributors include: Board of Curriculum Directors And the teachers who took care of the students in the course included 2 people. The tools used to collect data were structured interviews. And record form Analysis of data by content analysis. From the literature review and the interview, it is important to: 1. The management of the curriculum consists of three elements: 1) The curriculum of the educational institution consists of the appointment of the curriculum committee. Data analysis Documents and needs of learners Curriculum development Proposing the committee to approve Curriculum And research and follow-up. 2) The promotion of educational institution support consists of personnel development. Supporting budgets, engaging operational resources And 3) The quality supervision at the school level consists of supervising the curriculum, Internal Quality Assurance, Research and follow-up. 2. The operating conditions of the program for promotion and development of students with special musical abilities of Wat Sutthivararam School.